TEACHING EMBROIDERY FROM FOLK CRAFTS - F. Yusufkhodjayeva,; G. Jakupova, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, as a result of the attention given to our national art in Uzbekistan, we should increase the sense of respect for our national values among young people, and contribute to the development of our national embroidery. it is taken into account that he acquires a decent profession, makes a valuable contribution to the development of society, lives, and thereby manifests his identity in society, that is, matures as a person. Vocational education in a broad sense means that a person receives education in a trade according to his mental abilities, physical capabilities, abilities, interests and aspirations for this or that field, as well as values and worldviews, and then enters and adapts to this field. finally, it is understood that he will develop into a mature and qualified specialist over the years, and his main criterion at the current stage of quality education is to study the technology of collective creative works in practice.